1984
DOI: 10.1159/000233553
|View full text |Cite
|
Sign up to set email alerts
|

IgA Antibody Produced by Local Presentation of Antigen in Orally Primed Rats

Abstract: The effect of the introduction of antigen by gastric intubation on the locally stimulated mammary gland IgA antibody (Ab) response was examined. Rats receiving a particulate DNP antigen by gastric intubation prior to injection in the vicinity of the mammary glands (MGV) demonstrated increased levels of IgA Ab in milk. Soluble DNP antigen introduction by gastric intubation did not lead to increased IgA Ab levels in milk. Prior administration of either form of DNP antigen by gastric intubation did not affect the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1984
1984
1997
1997

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…5). Likewise, we have recently found that gastric intubation of DNP-BGG-Pa generally elicited a greater salivary IgA re sponse than did equivalent doses of DNP-BGG, also indicating that differences in antibody responses fol lowing gastric administration are due to the soluble and particulate nature of the antigens [35].…”
Section: Discussionmentioning
confidence: 78%
“…5). Likewise, we have recently found that gastric intubation of DNP-BGG-Pa generally elicited a greater salivary IgA re sponse than did equivalent doses of DNP-BGG, also indicating that differences in antibody responses fol lowing gastric administration are due to the soluble and particulate nature of the antigens [35].…”
Section: Discussionmentioning
confidence: 78%
“…In mammals, particulate antigens are predominantly transported by M cells, whereas the same antigen in soluble form mainly disappears from the lumen throughout the gut. Probably, as a consequence, particulate antigens can give a more prominent mucosal immune response than soluble antigens (Cox & Muench, 1984;Jeurissen et al, 1985). In this respect the absence of a mucosal immune response against fed ferritin is not surprising because most of the antigen may leave the gut lumen in the first segment.…”
Section: Discussionmentioning
confidence: 99%